Chronic Inflammation and Neutrophil Activation as Possible Causes of Joint Diseases in Ballet Dancers. (20th February 2014) - Borges, Leandro da Silva; Bortolon, José Ricardo; Santos, Vinicius Coneglian; de Moura, Nivaldo Ribeiro; Dermargos, Alexandre; Cury-Boaventura, Maria Fernanda; Gorjão, Renata; Pithon-Curi, Tania Cristina; Hatanaka, Elaine
Abstract : Herein, we investigated the effects of a ballet class on the kinetic profiles of creatine kinase (CK) and lactate dehydrogenase (LDH) activities, cytokines, complement component 3 (C3), and the concentrations of immunoglobulin (Ig), IgA and IgM, in ballerinas. We also verified neutrophil death and ROS release. Blood samples were taken from 13 dancers before, immediately after, and 18 hours after a ballet class. The ballet class increased the plasma activities of CK-total (2.0-fold) immediately after class, while the activities of CK-cardiac muscle (1.0-fold) and LDH (3.0-fold) were observed to increase 18 hours after the class. Levels of the TNF- α, IL-1 β, IgG, and IgA were not affected under the study conditions. The exercise was found to induce neutrophil apoptosis (6.0-fold) 18 hours after the ballet class. Additionally, immediately after the ballet class, the neutrophils from the ballerinas were found to be less responsive to PMA stimulus. Conclusion . Ballet class was found to result in inflammation in dancers. The inflammation caused by the ballet class remained for 18 hours after the exercise. These findings are important in preventing the development of chronic lesions that are commonly observed in dancers, such as those with arthritis and synovitis.